Pengembangan VCD pembelajaran teknik dasar shooting bolabasket pada siswa SMA di Pinrang - Abraham Abraham; Wahyu Jayadi (Seminar Nasional LP2M UNM, 2019)
This study aims to develop a basic basketball learning technique VCD that can help accelerate the process of understanding students in learning the basic techniques of shooting properly and correctly. This study uses a research method using a development research model from Borg and Gall. The subjects involved in this development research were: the subjects of the field test were 32 students of class X SMA 3 Pinrang. The data analysis technique used is qualitative and descriptive analysis techniques in the form of percentages. The results of the study indicate that the final form of the product developed after revision needs to be examined for its existence, because after going through several research processes there are several things that need to be corrected. The product of the development of VCD shooting learning in class X students of SMA 3 Pinrang can be used as one of the learning media alternatives that can be used in the learning process of Penjas in the 3 Pinrang Public High School in particular. This development product contains examples of good ways to do basic shooting techniques, types and aspects of basic shooting techniques and some small examples of variations in basic shooting techniques. The advantages of learning media in the form of VCDs are: 1) learning media in the form of VCDs displaying movements and repetitions consistently, 2) all students can see the full sequence of material and variations in the video, 3) can present information in a simultaneously and at the same time with sufficient capacity and amount, 4) can be designed as an independent learning media in accelerating the process of understanding basic shooting techniques because the resulting VCD can be played anytime and anywhere as desired, 5) can provide educational and entertaining presentation.